Cultural encounters during the LBII and IAI: Hittites and “Pelesets” in the Amuq (Hatay) Turkey - Marina Pucci (Asia Anteriore Antica)
The analysis of long-dormant archaeological documentation and recent archaeological discoveries concerning the Amuq region (modern Hatay) have shed new light on the period from the Late Bronze Age II to the Iron Age III, reopened old questions concerning the passage from the Late Bronze to the Iron Age, and contributed important historical data to the first centuries of the Iron Age I. This article investigates a specific feature in the debate on the LBA-IA transition, i.e. changes in the material culture that have been linked to the arrival of a non-local culture as a consequence of conquest or migration; in particular it investigates archaeological evidence from the sites of Chatal Höyük, Tell Tayinat and Alalakh, which has been employed by scholars as proof to support both the annexation of the land of Mukiš to the Hittite Empire during the Late Bronze Age II, as well as the arrival of foreign peoples from the Mediterranean during the Iron Age I.